The Sun is Love, a song cycle by Gwyneth Walker - Meeks, Madison (Kansas State University, 2023)
Composers have found depth and meaning in poetry for years. They hear metrical and dynamic shaping in the delivery of prose with one writer sharing that, “Of him who is giving a musical setting to a piece of verse it is demanded also that he shall clothe the poem in a fitting musical garb, adequately express the sense of the words, reproduce the atmosphere, and reveal the hidden meaning (if the poem have any).”¹. Gwyneth Walker has created this style of composition in The Sun is Love, which represents themes of nature with spiritual undertones. This document will focus on the compositional practices of Gwyneth Walker represented within the song cycle, The Sun is Love. These include text painting based on the naturalistic and spiritual qualities of the text and how she uses sound to take the audience on an aural journey. The first chapter is dedicated to describing the life and compositional practices of Gwyneth Walker to provide a foundation from which to analyze her works. Chapters 2-7 will focus on each individual movement of The Sun is Love using the following framework to deliver the content: song analysis, pedagogical considerations, poetic analysis. In the final chapter, I will share tips for future performers, ideas for textual analysis, and trends in story delivery within Walker’s works. Finally, I will offer my own thoughts on this process, what I have learned about the research and pedagogical process, and how this experience has changed me as a teacher, musician, and performer.
Keywords: Gwyneth Walker; Rumi; Sun is Love; Vocal music; Song cycle